Administrative Empowerment and its Relation with Organizational Commitment of School Principals in Mafraq Governorate from their Point of View - Mutleq, Eman Ahmad (Journal of Educational and Psychological Sciences, 2020)
This study aims to identify the level of administrative empowerment and its relation with organizational commitment of the school principals in Mafraq governorate from their point of view. The researcher used the descriptive survey, the study consisted tool in the questionnaire was distributed to a total random simple sample of (150) male and female directors. For the purposes of the study, a questionnaire consisting of (30) paragraph was used: the results of the study reveal that empowerment has an overall average (3.75 out of 5) with a (high) degree, on the themes levels, the delegation of authority received the highest average (3.89), followed by the team work with an average of (3.85) both of them (with high level) and the third theme self-motivation with an average (3.50) (with medium) degree. While the overall average of the organizational commitment was (3.83 out of 5) with a commitment level (high), the normative commitment level received the highest average (3.92), followed by sensation commitment with an average of (3.84) and finally, the continuity commitment (3.73), all of which were rated (high). The presence of a positive and statistically significant relationship between administrative empowerment and organizational commitment amounted (0.899) which indicates a (very strong) relationship. Based on the results of the study.Based on the results of the study, the researcher recommended the need to promote the culture of administrative empowerment in educational institutions, and to strengthen the organizational commitment and awareness of its importance.
Keywords: administrative empowerment; organizational commitment; school principals